Clima organizacional e cultura escolar: desafios da mudança no cotidiano escolar - Lopes, Tex Jones Correia (2013)
The master dissertation has proposed a reflection on the school routine, its organizational climate and culture, from the phenomenal representations of their practices and inter actions that occur day by day in the school producing some resistances that may obstruct changes. For such investigation the guiding question of the research was: how organizational climate and school culture can be elements of resistance to changes in daily school life? Conducted in a unit of a municipal school in the city of Santos, which offer the regular basic education (1st to 5th grade) and EJA (Education for Youth and Adults)the investigation was based on the observation, analysis and reflection, reported in experience of the manager and the social practices of everyday school life, including the period from 2010 to 2012. This is a qualitative research, which the methodological foundation is the historical-materialist dialectics, that sought to bring a sociological and philosophical conception about the school, as well as on its daily practices. Starting from the literature to reflect the theme, the theoretical framework was based on Julia (2001), and Forquin (1993) who focus their studies in the school culture as a historical object and the practices and school experiences; Nóvoa (1992), Glatter (1999), Libâneo (2004), Luck (2010) suggest a investigative analysis on the school as an organizational space; Heller (1992) and Kosik (199) by the reflective and philosophical analysis about man and everyday life by exposing the dialectic of cultural phenomena as objects of practical activity of man in history. The reflections pointed to the fact that without building awareness of the historical subject, who is able to overcome the world of appearance, the phenomenal reality isn´t manifested in all its dimensions. The ancient practices, not reflective, immersed in everyday life, manifested in resistance, often did not allow a dialogue and construction of a more complex and critical consciousness about the reality between subjects.